Correction to: Ultra-thin CdTe film properties enhancement via eco-friendly MgCl2-assisted thermal treatment (Journal of Optics, (2024), 53, 5, (4690-4697), 10.1007/s12596-023-01621-z) - Islam M.A.; Nur-E-Alam M.; Muhamad Hatta S.F.W.; Mohafez H.; Misran H.; Wahab Y.A.; Chowdhury Z.Z.; Soin N.B. (Springer, 2025)
In this article the affiliation ?School of Science, Edith Cowan University, Joondalup, WA, Australia? for Author Mohammad Nur-E-Alam was missing. ? The Author(s) 2024.